Financial impacts of the COVID-19 pandemic on the acquisition of basic component drug in a municipality in the interior of Bahia-Brazil (Research, Society and Development, 2021)
The pandemic caused by the new coronavirus, SARS-CoV-2, has established an alarming reality for every organization concerned with health. The pharmaceutical sector was one of the most affected, suffering direct impact due to the lack of supply of medicines, supplies and related products. The unpredictable cost and exacerbated inflation to health items have overtaken all other sectors of the economy, impacting directly the users of the Brazilian Health System (SUS). Thus, the objective of this research was to identify and analyze the impacts of the COVID-19 pandemic on the purchase of medicines of the basic component in the municipality of Vitória da Conquista-Bahia. The samples used in the study were collected through the official register of the municipality by means of the bidding protocol of the medicines listed in the Municipal Essential Medicines Lists (REMUME) in the years 2018, 2019 and 2020. The investigation was characterized as a documentary research, with a qualitative-quantitative approach. A total of 96 medicines were analyzed, since the anti-hypertensive drugs were the ones that remained constant, in other words, there was no decrease in the quantity bid for, bearing in mind that some medicines failed due to urgency and high demand, requiring a legal opinion for them to be purchased. The COVID-19 pandemic has negatively impacted the purchase of medicines in the municipality of Vitória da Conquista, causing around 11 medications above 30,000 items to undergo economic-financial rebalancing and having many failed bids leading to a shortage of some medications for months, thus having the need to train managers to better articulate with the global market.